ANALISIS PENGEMBANGAN KETERAMPILAN SOSIAL ANAK DI TK PERTIWI 1 PONTIANAK BARAT - Resha, .; Marmawi, .; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe development referred to in this study is a stage that occurs in children aged 5-6 years who have the ability to socialize with others so that it can develop in the next stage. Social skills referred to in this study is a capability possessed by a child acquired in the learning process and can be used in socializing in the environment. The development of social skills include: a) Respect for others , Respecting others is an attitude of respect for each other regardless of the person's status. b) Demonstrates Enthusiasm in Competitive Gaming Positively, Competitive game is a game that directs the child in playing freely and has rules so that children are eager in doing so. c) Shows Tolerance, The attitude shown by the child in associating with his friend mutual respect and happy to socialize with his friends without distinguishing one friend to another. d) Obey the Rules That Are Applied In A Game, Rules are a predetermined and must be followed. The rules that apply to play in a game means the way of play that has been set in the perminan and must be followed. e) Be Co-operative with Friends, Cooperation is the same as cooperative which means doing something together by helping each other as a team.. f) Know the Rules and Polite Conduct with Local Social Cultural Values, Manners are the customs of manners that are agreed upon in the local social environment. Manners consist of order and manners. Tata means custom, rules, norms, rules. Krama means manners, actions, actions. g) Appreciate other people's interests, Respecting the superiority of others will bring good to those who value and appreciate. Who appreciate learning that there is created an advantage over a person for His gift and how much more Almighty the Almighty created it. The cherished will also learn to be grateful for the favors of His gift and keep humble for what it has. Keywords: Development and social skills